Pemberdayaan Masyarakat Pada Ibu Rumah Tangga Dalam Meningkatkan Kemampuan Berwirausaha dan Membuka Peluang Usaha Berbasis Digital di Rusunawa Purus Kota Padang - Vika Fania Ayu Melani; Yohanna Maharani Jelita; Yudistira Ananda; Yulia Hanoselina (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The development of technology in the era of the industrial revolution has opened up various new opportunities, one of which is in the field of digital entrepreneurship. The use of digital platforms such as Shopee, Tokopedia, and Instagram has become an effective means of marketing products, including for housewives. Empowering housewives in the field of digital entrepreneurship is important to improve economic independence and the standard of living for families. This activity aims to provide basic knowledge and skills regarding digital entrepreneurship to housewives living in Rusunawa Purus, Padang City. The method used in this activity is a qualitative descriptive approach through interactive socialization, consisting of material presentations, discussions, Q&A, and hands-on practice. The results of the activity showed that participants demonstrated high enthusiasm, began to understand the concept of digital entrepreneurship, and were motivated to start home-based online businesses. This activity proves that empowerment through digital training can be an effective strategy to increase the economic participation of housewives. Continued mentoring is needed so that the digital transformation process can be sustainable and provide real economic impact.